2022
DOI: 10.1002/emp2.12739
|View full text |Cite
|
Sign up to set email alerts
|

Impact of a rapid high‐sensitivity troponin pathway on patient flow in an urban emergency department

Abstract: Study Objective: To evaluate whether the introduction of a 1-hour high-sensitivity cardiac troponin-T (hs-TnT) pathway for patients who present to the emergency department (ED) with suspected acute coronary syndrome (ACS) improves ED patient flow without changing the rate of "missed" major adverse cardiac events (MACE), compared to use of conventional cardiac troponin with an associated 3-hour pathway.Methods: This was a prospective, uncontrolled observational study conducted before and after implementation of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
0
1
0
Order By: Relevance
“…sition decision time, which remained almost unchanged: 4.7 hours before and 4.8 hours after the implementation of the new algorithm 70. In an attempt to investigate the clinical feasibility of the ESC 2020 rapid 0/1 h algorithm, Couch et al found many practical limitations of achieving the 1 h target for the repeated Tn sampling, mainly related to the need for the second blood draw prior to obtaining the results of the first blood draw in the real-life settings of the ED 71.…”
mentioning
confidence: 98%
“…sition decision time, which remained almost unchanged: 4.7 hours before and 4.8 hours after the implementation of the new algorithm 70. In an attempt to investigate the clinical feasibility of the ESC 2020 rapid 0/1 h algorithm, Couch et al found many practical limitations of achieving the 1 h target for the repeated Tn sampling, mainly related to the need for the second blood draw prior to obtaining the results of the first blood draw in the real-life settings of the ED 71.…”
mentioning
confidence: 98%